Investigating value added from heritage assets: An analysis of landmark historical sites in Wales. (6th August 2018) - Beynon, Malcolm J.; Jones, Calvin; Munday, Max; Roche, Neil
Abstract: We reveal how tourist visitation to similar historical sites supports different levels of local gross value added (GVA). The paper shows how information on tourism activity at few historical sites can be used to analyse causal recipes defining whether sites support relatively high/low levels of GVA. Fuzzy‐set qualitative comparative analysis is employed to offer perspectives not possible with other analytical methods. The study reveals that for a set of similar heritage sites, that factors supporting local economic impacts are complex and with this having ramifications for management interventions around sites that seek to boost the economic impacts of visitation.